Phylogeography suggest the Yili Valley being the glacial refuge of the genus Ixiolirion (Amaryllidaceae) in China. Issue 4 (19th May 2019) - Li, Yan; Song, Feng; Zhang, Xue-Ni; Lv, Guang-Hui
Abstract : The Pleistocene climatic oscillations had profound effects on the demographic history and genetic diversification of plants in arid north-west China where some glacial refugia have been recognized. The genus Ixiolirion comprises three species, of which two, I. tataricum and I. songaricum (endemic), occur in China. In some locations they are sympatric. We investigated their population structure and population history in response to past climatic change using a sample of 619 individuals in 34 populations with nITS and ptDNA sequences. A significant genetic divergence between the two species was supported by a high level of pairwise genetic differentiation, very low gene flow, and phylogenetic analysis showing that I. songaricum haplotypes were monophyletic, whereas those of I. tataricum were polyphyletic. We found significant differentiation and phylogeographic structure in both species. The split of the two species was dated to the late Miocene (∼7 Ma), but deep divergence occurred in the mid-late Quaternary. A similar haplotype distribution pattern was found in both species: one to two dominant haplotypes across most populations, with unique haplotypes in a few populations or a geographic group. The genetic diversity, haplotype number, and haplotype diversity decreased from the Yili Valley to the central Tianshan and Barluk Mountains. Additionally, ptDNA analysis showed that I. tataricum diversified in the eastern Tianshan and Barluk Mountains, which might be due to physical barriers to long distance seed dispersal such as desert. In conclusion, our results indicated that the Yili Valley was likely a glacial refuge for Ixiolirion in China, with postglacial dispersal from the Yili Valley eastward to the eastern Tianshan Mountains, and northward to the Barluk Mountains. The climatic changes in the Miocene and Pleistocene and geographic barriers are important factors driving species divergence and differentiation of Ixiolirion and other taxa.